2002
DOI: 10.1046/j.1365-2389.2002.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil pH on denitrification: progress towards the understanding of this interaction over the last 50 years

Abstract: Summary Results from the pioneering research on the interactions between pH and denitrification in soil from the 1950s to the present are reviewed, the changing perceptions of this complex relationship are discussed, and the current status of the subject is assessed. Facets of this relationship that are analysed in detail include the direct or indirect influence of pH on overall denitrification rates in soils, changes in the composition of gaseous products that depend on pH, methods for measuring the process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
390
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(413 citation statements)
references
References 48 publications
(86 reference statements)
20
390
3
Order By: Relevance
“…N 2 O emissions were negatively correlated (P < 0.1) with soil pH in both the full study period and the growing season 2006 models (Table 3a and b).The optimum pH from denitrifiers is often thought to be between approximately 6.5-8.0 (Knowles, 1981;Šimek and Cooper, 2002), therefore any increase above the mean catchment pH of 4.18 should theoretically increase N 2 O production. However the partitioning of N 2 O and N 2 is also influenced by pH with a higher proportion of N 2 O in more acid conditions (Šimek et al, 2002).…”
Section: Effususmentioning
confidence: 97%
“…N 2 O emissions were negatively correlated (P < 0.1) with soil pH in both the full study period and the growing season 2006 models (Table 3a and b).The optimum pH from denitrifiers is often thought to be between approximately 6.5-8.0 (Knowles, 1981;Šimek and Cooper, 2002), therefore any increase above the mean catchment pH of 4.18 should theoretically increase N 2 O production. However the partitioning of N 2 O and N 2 is also influenced by pH with a higher proportion of N 2 O in more acid conditions (Šimek et al, 2002).…”
Section: Effususmentioning
confidence: 97%
“…N 2 O emission is correlated with soil Eh (Kralova et al 1992;Masscheleyn et al 1993;Wlodarczyk et al 2003;Yu and Patrick 2003), and with soil pH as pH influences the three most important processes that generate N 2 O and N 2 : nitrification, denitrification, and dissimilatory NO 3 -reduction to NH 4 + (Simek and Cooper 2002). Eh and pH also interact in determining N 2 O and CH 4 emission: the Eh range with minimum N 2 O and CH 4 production shifts to lower values of the Eh scale when pH increases (Yu and Patrick 2003).…”
Section: Soil Eh and Ph And Soil Genesismentioning
confidence: 99%
“…In soil science, for instance, despite the recognition of the importance of Eh, pH is often regarded as the master variable (Brady and Weil 2010;Simek and Cooper 2002). This is also the case in plant physiology (Rengel 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Results based on field and laboratory studies (Simek and Cooper, 2002) determinede that denitrification processes measured in cold salt marshes would not be a significant source of N 2 O. These authors showed that denitrification end products were mostly determined by sediment pH with low N 2 O/N 2 production ratios in more neutral sediment.…”
mentioning
confidence: 99%